Valoración Financiera Mediante el Método De Flujo – Caja Descontado a la Empresa “Destalladora Cevallos”, Cantón Cevallos, 2020 – 2022 - Tipan Bonilla, Karen Dayana (2024)
ABSTRACT: The present research aims to perform a financial assessment using the discounted cash flow method for the company "Destalladora Cevallos" from 2020 to 2022 to determine the company's real value as of the specified date. For the development of this research, the problem was considered that the company in question did not know its financial value. A descriptive study was supported by the analytical method of content analysis of documentary sources, investigating both conceptual and historical-financial behavior of the company being financially evaluated and future prospects and information provided by the company itself. This methodology allows for the elaboration of calculations and financial projections to determine the company's financial value. To determine the financial value of the company, indices such as inflation and GDP (Gross Domestic Product), based on a database from 2019 to 2022, were considered to make projections for 2023 to 2027, resulting in an average projected rate of 2.18%, which was essential for the valuation calculation. Additionally, the discount rate was 7.82%, and the Consumer Price Index (CPI), wage rate, and fiscal sector were also calculated, resulting in a final market value of $865,204. Based on the results, it can be determined that Destalladora Cevallos is at an acceptable value according to the financial assessment. Keywords: Financial Valuation, Discounted Cash Flow Method, Destalladora Cevallos, Projections.